2019
DOI: 10.28940/terra.v37i2.479
|View full text |Cite
|
Sign up to set email alerts
|

Hongos formadores de micorrizas arbusculares (HFMA) como estrategia para reducir la absorción de cadmio en plantas de cacao (Theobroma cacao)

Abstract: Colombia is among the countries of Latin America that produce about 80% of f ine or “prime” cocoa of the world; however, cocoa in Colombia has limitations related to the presence of cadmium (Cd) in some soils where it is grown and this reduces the safety of the product. The objective of this study was to evaluate the absorption of cadmium in a cocoa pattern (IMC 67) in association with arbuscular mycorrhizal fungi (AMF) to determine their potential use as Cd immobilizers in medium and long-term. A randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
3
0
3
Order By: Relevance
“…Alarcón et al [42], mentioned that when inoculating Solanum lycopersicum L. with Glomus mosseae, it favored growth indicators and reduced infestation by the nematode Meloidogyne spp. Other authors such as Perez-Moncada [43], reported that inoculation with three types of Glomus macrocarpum and one of Rhizoglomus intraradices decreased the absorption of cadmium in Theobroma cacao L. plants, registering the above as benefits to reduce stress in the plant. Evaluations carried out [44], with Rhizophagus aggregatus and a consortium of Glomus claroides, Rhizophagus diaphanous, and Paraglomus albidum on seedlings of varieties of Coffea arabica L. showed that inoculation with the consortium registered the highest values in seedling growth, phosphorus assimilation, and health.…”
Section: Discussionmentioning
confidence: 78%
“…Alarcón et al [42], mentioned that when inoculating Solanum lycopersicum L. with Glomus mosseae, it favored growth indicators and reduced infestation by the nematode Meloidogyne spp. Other authors such as Perez-Moncada [43], reported that inoculation with three types of Glomus macrocarpum and one of Rhizoglomus intraradices decreased the absorption of cadmium in Theobroma cacao L. plants, registering the above as benefits to reduce stress in the plant. Evaluations carried out [44], with Rhizophagus aggregatus and a consortium of Glomus claroides, Rhizophagus diaphanous, and Paraglomus albidum on seedlings of varieties of Coffea arabica L. showed that inoculation with the consortium registered the highest values in seedling growth, phosphorus assimilation, and health.…”
Section: Discussionmentioning
confidence: 78%
“…El estudio de Bhaduri & Fulekar (2012) estableció el potencial fitorremediador de Ipomoea aquatica en suelos moderadamente contaminados por Cd, el cual muestra mejor acumulación en tejidos vegetales cuándo se inocula con HMA, la acumulación es de hasta 100 mg/l y 88,07 %, sin síntomas visuales de toxicidad, mientras que las plantas sin HMA muestran una marcada reducción del crecimiento a la misma concentración con una acumulación de metal de 73,2 %. Por otro lado, Glomus macrocarpum y Rhizoglomus intraradices son capaces de aliviar el estrés por Cd en cultivos de cacao, por la traslocación de este a todos los órganos (tallos, hojas y raíces) y no al grano de cacao que es de importancia económica en muchos países (Pérez et al, 2019). El Higo Revista Científica / Volumen 12.…”
Section: Participación De Los Hma En Suelos Contaminadosunclassified
“…Los hongos micorrizas arbusculares (HMA) han demostrado ser una alternativa biotecnológica que permite optimizar los recursos, ofreciendo un sinnúmero de beneficios como una mejor tolerancia a los factores de estrés abióticos (Porcel et al, 2012), biorremediación por la acumulación de metales pesados (Pérez et al, 2019), bioprotección (Mohamed et al, 2019) su particular sistema radicular los convierte en un aliado natural para la fertilización (Durán et al, 2013). Además, tiene un efecto directo en el ecosistema, ya que mejoran la estructura y agregación del suelo (Barbosa et al, 2019); su asociación incrementa el crecimiento del huésped y cambia los niveles morfológicos, fisiológicos y nutricionales de las plantas (Muñoz, 2018).…”
Section: Introductionunclassified
“…The potential of AMF G. margarita and Acaulospora tuberculata, as well as the strain (PR11) of T. asperellum , promoted cocoa growth and induced resistance against P. megakarya in Cameroon [ 96 ]. Recent studies have shown the beneficial effects that AMF from Colombian cocoa soils to alleviate the stress that T. cacao plants show when translocating heavy metals such as cadmium [ 103 ]. In addition, G. margarita and A. tuberculata significantly reduced susceptibility to P. megakarya in the hybrid genotypes of the F79SA hybrid family of T. cacao [ 104 ].…”
Section: Preharvestmentioning
confidence: 99%